2015
DOI: 10.5194/hess-19-4411-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Three Gorges Dam, the South–North Water Transfer Project and water abstractions on the duration and intensity of salt intrusions in the Yangtze River estuary

Abstract: This paper assesses the impacts of the Three Gorges Dam, the South-North Water Transfer Project and other water abstractions on the probability of long-duration salt intrusions into the Yangtze River estuary. Studies of intrusions of saltwater into estuaries are typically constrained by both the short duration of discharge records and the paucity of observations of discharge and salinity. Thus, studies of intrusions of saltwater into estuaries typically seek to identify the conditions under which these intrusi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Early reviews noted that decreased flow in the Yangtze Basin could worsen the already existing problem of estuary salinization (e.g., [3,9]). These findings were confirmed by Chen et al [11] who found that the ER-SNWTP alone could increase estuary salinization between January and February, as well as Webber et al [37] who carried out a broader analysis of Yangtze Estuary salinization. A similar pattern connects the water losses caused by MR-SNWTP to riparian health along the Han River, from which the MR-SNWTP originates [13,38].…”
Section: Environmental Impactssupporting
confidence: 75%
See 1 more Smart Citation
“…Early reviews noted that decreased flow in the Yangtze Basin could worsen the already existing problem of estuary salinization (e.g., [3,9]). These findings were confirmed by Chen et al [11] who found that the ER-SNWTP alone could increase estuary salinization between January and February, as well as Webber et al [37] who carried out a broader analysis of Yangtze Estuary salinization. A similar pattern connects the water losses caused by MR-SNWTP to riparian health along the Han River, from which the MR-SNWTP originates [13,38].…”
Section: Environmental Impactssupporting
confidence: 75%
“…The Han River will experience declines in discharge [13], while the communities who rely on it will continue to grow and demand more water. Yangtze Estuary salinization will grow worse, especially during dry months and years, further increasing the environmental concerns in this already critical region [11,37]. Although the contention that, on balance, the socio-ecological costs in water-providing areas will be outweighed by the benefits in water-receiving areas on a national scale (e.g., [25]) seems plausible, these aggregate effects are likely of little consolation to those who will be negatively impacted by the implementation of this program.…”
Section: Scale Effects and Water Sustainabilitymentioning
confidence: 99%
“…, Hutchinson , Webber et al. ) illustrate the potential for saltwater barrier removal to alleviate this effect.…”
Section: Swi Restoration Goals and Toolsmentioning
confidence: 99%
“…Early research on China's SNWTP focused primarily on its economic viability and projected social and environmental effects (Wilson et al, 2017, have a full review), while in recent years, there have been two primary lines of enquiry in English language publications. The second line of enquiry concerns the SNWTP's physical impacts, primarily the modelling or direct measurement of hydrological impacts (see Ma et al, 2016;Webber et al, 2015;Yan et al, 2012;Ye et al, 2015) and pollution flows (Zhang et al, 2018). While these studies do point to the far-reaching and unequal social, economic, political, and environmental effects of the SNWTP, particularly in source regions, their focus is the power struggles embedded in the SNWTP.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies do point to the far-reaching and unequal social, economic, political, and environmental effects of the SNWTP, particularly in source regions, their focus is the power struggles embedded in the SNWTP. The second line of enquiry concerns the SNWTP's physical impacts, primarily the modelling or direct measurement of hydrological impacts (see Ma et al, 2016;Webber et al, 2015;Yan et al, 2012;Ye et al, 2015) and pollution flows (Zhang et al, 2018). There is limited dialogue between those undertaking such approaches, and as a result, no integrated account of the geographic implications, both human and physical, of this massive interbasin transfer.…”
Section: Introductionmentioning
confidence: 99%